THE STRATEGIC IMPORTANCE OF THE DEVELOPMENT OF THE MEDICAL SECTOR IN KYRGYZSTAN IN THE LATE 19TH – EARLY 20TH CENTURIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article describes the significant work done in public health in Kyrgyzstan from the late 19th to the early 20th centuries. Of particular significance was the arrival of the first Russian doctors and medical centers in the region, particularly during the Russian Empire. The article states that during the Turkestan Governorate-General, research was conducted on infectious diseases among the population throughout the territory of Kyrgyzstan and, on this basis, much attention was paid to epidemiological and sanitary work. It was also emphasized that initially a policy of providing medical care and preventive measures to Russian peasant settlers was pursued. It was established that several articles by Russian researchers on the spread of infectious diseases in Kyrgyzstan were published before the October Revolution. The author noted that after the establishment of Soviet power, medical care in our country improved significantly. Particularly after the formation of the Kara-Kyrgyz Autonomous Region, medical schools, clinics with technical equipment, and hospitals were built in some regions, and vaccination efforts began. The article demonstrates that, thanks to such efforts, epidemic diseases have been completely eradicated in the Kyrgyz Republic.
Keywords: Russian Empire, medicine, infectious diseases, vaccination, healthcare, health, etc.